Dampak Pelaksanaan Sistem Pemerintahan Feodalisme terhadap Pembentukan Sistem Stratifikasi Sosial (Shinokosho) pada Zaman Edo - Sri Dewi Andriani (Bina Nusantara University, 2011)
Tokugawa governance is military rezime government in Japan during 17th to 19th century. The governance was led by a general or known as shogun helped by daimyo or the head of district governance or han. Shogun was held hereditary by Tokugawa family. Japan military governance applied tightened inspection for the people to maintain the power. One of well-known stratification community social system is shinokosho, which divided people into four social classes: military, farmer, trader, and artisan. The research will discuss problems in the effects of feodalism governance system towards the formation of social stratification system shinokosho. The research methods used are descriptive, analitic and qualitative. The result is that the application in this tightened system made people could not change status that finally made Tokugawa family hereditary could have the governance power for more than 250 years.